TEPaaS: test execution platform as-a-service applied in the context of e-health. (17th July 2019) - Lahami, Mariam; Krichen, Moez; Alroobaea, Roobaea
Runtime testing of large-scale systems running in dynamic and distributed environments is a costly and a resource consuming task. With the aim of handling such runtime validation activity in a cost effective manner, we introduce in this paper a scalable test execution platform deployed on the cloud, called test execution platform as-a-service (TEPaaS). The latter offers various testing capabilities provided as services like automatic test component deployment, test execution and test evaluation. A proof-of-concept prototype is developed and deployed on the Google cloud platform and also evaluated through several experiments. Based on this prototype, we validate an e-health case study implemented using web service technology and also deployed on the cloud.